Two Novel Mutations Associated with Polymyxin-B Resistance in a Pandemic Lineage of Uropathogenic Escherichia coli of the Sequence Type 69 - Dos Santos, Carla Adriana; Hernandes, Rodrigo Tavanelli [UNESP]; Cunha, Marcos Paulo Vieira; Nagamori, Filipe Onishi; Gonçalves, Claudia Regina; Sacchi, Claudio Tavares; Tiba-Casas, Monique Ribeiro; Camargo, Carlos Henrique (Karger Publishers, 2021)
Background: Uropathogenic Escherichia coli (UPEC) are frequent pathogens worldwide, impacting on the morbidity and economic costs associated with antimicrobial treatment. Objectives: We report two novel mutations associated with polymyxin-B resistance in an UPEC isolate collected in 2019. Methods: Isolate was submitted to antimicrobial susceptibility testing including broth microdilution for polymyxin B. Whole genome was sequenced and analyzed. Results: Polymyxin-B total inhibition occurred at 16 mg/L (resistant). UPEC isolate was assigned to the phylogroup D, serotype O117:H4, and Sequence Type 69. mcr genes were not detected, but two novel mutations in the pmrA/basS (A80S) and pmrB/basR (D149N) genes were identified. Conclusions: The occurrence of non-mcr polymyxin resistance in E. coli from extraintestinal infections underscores the need of a continuous surveillance of this evolving pathogen.
Keywords: Antimicrobial resistance; Escherichia coli; Polymyxin B; Uropathogenic Escherichia coli; Whole-genome sequencing